Pharmacological prediction of Marchantia polymorpha: GC-MS and molecular docking approaches - Farhan, Abdillah Maulana (Universitas Muhammadiyah Surakarta, 2026)
Marchantia polymorpha is the liverworts that can be found abundantly in the Mount Pasang Jember area. The metabolite profiling of M. polymorpha has not yet been conducted. The method used in this study was untargeted metabolite profiling using GC-MS, and the results of the metabolite compound profiling were analyzed in silico using bioinformatics-based, namely PASS Online, SwisADME, and Molecular Docking using PyRx 8.0 with AutodockVina. The aims of docking with this protein was adjusted to the PASS Online results, namely alkenylglycerophosphocholine hydrolase inhibitor and antiseborrheic, which are closely related to antifungals. The natural metabolite compounds detected from M. polymorpha were fatty acids (20%), terpenoids (16%), and phenolics (10%). Terpenoids-phenolics compounds were analyzed in silico to predict pharmacological potential. Terpenoids showed that the compound with the highest Pa value was 3,7-Cyclodecadiene (Pa=0.920), predicted to be an alkenylglycerophosphocholine hydrolase inhibitor, while the phenolic compound with the highest Pa value was hydroquinone (Pa=0.927), predicted to be an antiseborrheic. Based on SwissADME in silico Druglikeness, five compounds out of a total of six terpenoid and phenolic compounds showed compliance with Lipinski's theory. In addition, the in silico results also showed a bioavailability score of 0.55. Molecular docking was performed on the target protein sterol 14-α-demethylase (CYP51) from Candida albicans (PDB ID: 5TZ1). This protein is representative of antifungal agents. The results of molecular docking showed that the compound 3,7-Cyclodecadiene consistently had the strongest binding affinity value of -10.1 kcal/mol with residues ILE A:55, ALA A:62, PHE A:58, and TRP B:5 These results imply that further research on M. polymorpha metabolites should be conducted using comprehensive methods to explore their potential in the field of health.